2006
DOI: 10.1007/s00535-006-1903-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal variation on the clinical course of chronic hepatitis B

Abstract: Seasonal variation might affect the clinical course of chronic hepatitis B. The role of seasonal triggering factors should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Ten studies included treated patients (although less than 10% of the cohort per inclusion criteria) and treatment status was unclear in 17 studies. In studies with treated patients, 4 included oral antivirals (35,56,62,81), 3 interferon therapy (20,35,38) and 4 either did not specify (26,65,72) or included older non-standard drugs (77). Co-infected patients were not excluded in 17 studies and either not reported or not tested in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies included treated patients (although less than 10% of the cohort per inclusion criteria) and treatment status was unclear in 17 studies. In studies with treated patients, 4 included oral antivirals (35,56,62,81), 3 interferon therapy (20,35,38) and 4 either did not specify (26,65,72) or included older non-standard drugs (77). Co-infected patients were not excluded in 17 studies and either not reported or not tested in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal variation in immunity has been found in healthy individuals and in association with some diseases [14]. There is paucity of data on effect of seasonal variation on prevalence of HBV and HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal reactivation of HBV might induce damage to hepatocytes and increase R249S release into the bloodstream in the weeks that follow reactivation. Seasonal hepatitis flare was described by Zhang et al (2006) in a longitudinal study of 2,238 subjects from the area of Guangzhou, China. In that study, acute exacerbation of hepatitis peaked during spring (March–May), and HBeAg seroconversion peaked during summer (June–August).…”
Section: Discussionmentioning
confidence: 99%